An analysis on the factors related to the adoption of KS tools - Lee, Angela Siew-Hoong; Lim, Tong-Ming; Thi, Lip Sam (2015)
KS tools are tools that allow knowledge workers to share and reuse knowledge both in organizations and leisure environments. However the adoption of KS tools in most organizational ecosystem is slow and worrying, as many researchers have pointed out.This study looks into several factors such as nationality, experience, position and education that influence the usage on a list of KS tools. The study will use technology adoption lifecycle proposed by Beal, Rogers and Bohlen [1] model explains the six (6) types of users in organizations.This paper will provide an analysis from data collected to explain the correlations between the factors discussed above and the usage level of the KS tools within their organizations using the theory of diffusion of innovation on different adopter categories [6]. This study uses survey to conduct an empirical investigation and our instruments are designed based on the several past well tested research studies.